PDI Knockdown Inhibits Seizure Activity in Acute Seizure and Chronic Epilepsy Rat Models via S-Nitrosylation-Independent Thiolation on NMDA Receptor - Jeon, A. Ran; Kim, Ji-Eun (Frontiers in Cellular Neuroscience, 2018)
Redox modulation and S-nitrosylation of cysteine residues are the post-translational modifications of N-methyl-D-aspartate receptor (NMDAR) to regulate its functionality. Recently, we have reported that protein disulfide isomerase (PDI) has a proconvulsive role via reducing disulfide bond (S-S) to free thiol (-SH) on NMDAR. Since PDI is a modulator of S-nitrosylation on various proteins, it is noteworthy whether PDI regulates seizure activity by affecting S-nitrosylation of NMDAR. In the present study, we found that acute seizures in response to pilocarpine and spontaneous seizures in chronic epilepsy rats led to the reduction in S-nitrosylated thiol (SNO-thiol)-to-total thiol ratio on NMDAR, while they elevated nitric oxide (NO) level and S-nitrosylation on NMDAR. N-nitro-L-arginine methyl ester (L-NAME, a non-selective NOS inhibitor) did not affect seizure activities in both models, although it decreased SNO-thiol levels on NMDAR. However, PDI knockdown effectively inhibited pilocarpine-induced acute seizures and spontaneous seizures in chronic epilepsy rats, accompanied by increasing the SNO-thiol-to-total thiol ratio on NMDAR due to diminishing the amounts of total thiols on GluN1 and GluN2A. Therefore, these findings indicate that PDI may not be a NO donor or a denitrosylase for NMDAR, and that PDI may contribute to ictogenesis by the S-nitrosylation-independent thiolation on NMDAR.